22 Open vs. minimally invasive radical trachelectomy in early stage cervical cancer: international multicenter irta study results. (18th September 2019) - Salvo, G; Ramirez, PT; Wu, X; Leitao, M; Mosgaard, BJ; Falconer, H; Perrotta, M; Rendón, G; Kucukmetin, A; Berlev, I; Persson, J; Vieira, M; et al.
Abstract : Objectives: To compare disease-free survival (DFS) between patients who underwent open (ORT) versus minimally invasive (MIS) radical trachelectomy (RT) [laparoscopic (LRT) or robotic (RRT)]. Methods: Eligibility criteria included: 1) RT and pelvic lymphadenectomy with/without sentinel lymph node mapping, 2) 1/2005 to 12/2017 3) squamous, adenocarcinoma, or adenosquamous histology, 4) stage IA2-IB1, 5) tumors ≤2 cm, 6) 15 or more cases per center. Results: A total of 698 patients [open (n=388) vs. MIS (310)] were included. The median follow-up time was 40.9 months (range, 1–179.1) [MIS 38.6 (range, <1–128.1) vs. open 68.3 (range, <1–200.8) (p<0.001)]. MIS patients had smaller tumors (no visible lesion: 76.8% vs 57.0%, < 1 cm: 1.9% vs. 2.8%, 1–2 cm: 21.3% vs. 40.2%, p<0.001) and lower rates of residual disease (42.9% vs. 56.2% p<0.001). (table 1 ) There were no differences in rates of parametrial involvement (2.1% vs. 1.3% p=0.055), vaginal involvement (0.8% vs. 1.4% p=0.198), positive margins (2.9% vs. 3.5% p=0.766), or positive nodes (7.2% vs. 4.5%, p=4.02). (table 2 ) Patients who underwent open RT had longer hospital stay (6 (1–23) vs 2 (0–24) days, p<0.001) and received more adjuvant therapy (12.7% vs. 5.9%, p=0.003). MIS patients had more readmissions (11.0% vs. 1.8%, p<0.001) and reoperations (4.8% vs. 1.5%, p=0.01). There was no difference in recurrence rate (6.4% vs. 5.7%, p=0.7492), DFS (p=0.46) or OS (p=0.91) between MIS and open surgical approaches (figure 1 ). Conclusions: Surgical approach in radical trachelectomy for low-risk cervical cancer was not associated with differences in recurrence rates or survival. MIS had worse perioperative outcomes.